Exploring the Strategic Role of Brand Equity Towards Competitive Advantage in the Smartphone Industry - Hashim, Sharizal (Animo Repository, 2019)
This study intends to explore the strategic role of brand equity towards competitive advantage from the customer’s perspective in the context of the smartphone market in Kuching, a city located in Sarawak, Malaysia. Based on the two competitive advantage strategies (cost advantage and differentiation), this study aims to investigate the extent these two strategies affects brand equity prediction towards customer satisfaction. By employing convenience sampling, self-administered questionnaires were distributed among smartphone users. A total of 417 respondents were involved in the process. The data collected were further evaluated using the Statistical Package for Social Sciences (SPSS). Pearson’s correlation analysis, multiple regression analysis, and independent sampled t-test were used to perform statistical analysis. The results revealed that elements of Brand Equity (brand awareness, brand associations, perceived quality, and brand loyalty) have a positive relationship with customer’s satisfaction. There is also a significant difference between the two competitive advantage strategies, that is, cost advantage and differentiation. Results showed that when the elements of brand equity increase, customer satisfaction level also increases and the level of increment among two samples of study is different. This study contributes in a twofold manner. Brands can be effective tools for the organizations to gain their competitive advantage, but specific advantage and segment need specific brand treatment.